Senam Lansia Menurunkan Tekanan Darah pada Lansia - Andry Sartika; Betrianita Betrianita; Juli Andri; Padila Padila; Ade Vio Nugrah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine whether there is an influence of elderly exercise on decreasing hypertension in elderly who experience hypertension in Posbindu Cempaka Permai Bengkulu City. This study uses a pre-experimental method. The results showed in the intervention group, the average reduction in systolic blood pressure was 21.00 mmHg, from 171.50 mmHg to 150.50 mmHg. In contrast, the average reduction in diastolic blood pressure was 13.00 mmHg, from 103.00 mmHg to 90, 00 mmHg. Based on the t-dependent test results, obtained (p-value = 0,000) for systolic results and for diastolic results (p-value = 0,000). In conclusion, there is the influence of elderly exercise on decreasing blood pressure before and after the elderly's exercise in hypertensive elderly in Posbindu Cempaka Permai Bengkulu City. Keywords: Hypertension, Elderly Gymnastics, Blood Pressure